Strategi dan Praktik Konvergensi Media Pada Segmen Makarena dalam Program Sore Bara Harsya Sebagai Upaya Survival Radio Delta FM di Tengan Persaingan Industri Penyiaran - Laksmi Rachmaria; Yunita Rafika Dewi (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2018)
Abstract Limitations possessed by conventional media in serving the needs of media users such as radio, newspapers, magazines or television to adapt to the advancement of communication technology, if there is no concern from competition in the media industry. This study aims to determine the process of media convergence conducted by producer Sore Bara Harsya on the segment in the segment of Makarena. This study uses a qualitative approach and the Concept of Media Convergence Shierly Biagy. The subject of this research is the program of Bara Harsya Event Producer on Radio 99.1 Delta FM Jakarta. Data collection was obtained using non-participants and interviews with program producer Bore Harsya Sore to support interview data with Program Director and Digital Radio Content 99.1 Delta FM Jakarta. Other data about library creation, documentation, and internet. The results showed that in conducting the convergence process on the content of Makarena, the manufacturer has performed four stages which became the basis of consistent convergent media formation. Where the producers have done the stages (chain) applied in the form of maintenance or how to manage, the broadcast network is applied in the form of segmentation of Delta FM radio listener audience, then the conglomerate (conglomerate) used as a form of profit program for the company, and vertical integration (vertical integration ) is applied in the form of combining conventional media (radio) with digital media (youtube) as a form of target market openness. Amongst these stages, in managing content, Makarena Producer is more dominant than conglomerate and vertical as it can support its show program. Keywords: Radio, Content Program, Convergence Media